2007
DOI: 10.1158/0008-5472.can-06-3879
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and In vivo Molecular Evidence for Better Therapeutic Efficacy of ABT-627 and Taxotere Combination in Prostate Cancer

Abstract: Bone is the key metastatic site for prostate cancer. Endothelin 1 (ET-1) produced abundantly by prostate cancer cells binds to its receptor present on bone marrow stromal cells and favors osteoblastic response during bone metastases of prostate cancer. This suggests that interrupting ET-1 interaction with its endothelin A (ET A ) receptor could be useful for inhibiting prostate cancer bone metastasis and, as such, may enhance the therapeutic activity of docetaxel (Taxotere), the most commonly used drug for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 20 publications
0
58
0
1
Order By: Relevance
“…18 However, in the Scid-hu model, where prostate cancer cells are injected directly into human fetal bone explants, atrasentan alone was ineffective at blocking C4-2b prostate tumor growth; though it did enhance the antitumor efficacy of docetaxel. 19 Other studies indicate that ET-1 may also play a role in cancer beyond bone metastasis. ET-1 has been repeatedly shown to mediate survival and/or proliferation in cell-based assays, including prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…18 However, in the Scid-hu model, where prostate cancer cells are injected directly into human fetal bone explants, atrasentan alone was ineffective at blocking C4-2b prostate tumor growth; though it did enhance the antitumor efficacy of docetaxel. 19 Other studies indicate that ET-1 may also play a role in cancer beyond bone metastasis. ET-1 has been repeatedly shown to mediate survival and/or proliferation in cell-based assays, including prostate cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence suggests that endothelin-1 may reduce the rates of apoptosis in prostate cancer cell lines exposed to docetaxel, and endothelin-A blockade with atrasentan reduces the rate of tumor growth in preclinical models compared with docetaxel alone (13,14). Single agent phase III studies have not shown convincing evidence of clinical benefit in castration-resistant prostate cancer; however, given the complexity of the pathogenesis of tumor progression and bone microenvironment interactions, it is likely that combination therapy is needed in this disease (12,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The severe combined immunodeficiency (SCID)-human prostate cancer and breast cancer model of experimental bone metastasis was used for our study as described earlier (37)(38)(39). Briefly, suspensions of C4-2B cells were injected intraosseously by insertion of a 27-gauge needle through the mouse (Taconic Farms) skin directly into the marrow surface of the previously implanted bone (38,39).…”
Section: Methodsmentioning
confidence: 99%
“…11,[26][27][28]. In addition, the mice from group III received three doses of Taxotere (5 mg/kg body weight given intravenously) every 72 h after 24 h DIM gavaging (39,40). Group IV was exposed to DIM and treated with Taxotere as shown for groups II and III.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation